Research on the Deterioration Mechanism of PPF Mortar-Masonry Stone Structures Under Freeze–Thaw Conditions - Jie Dong; Hongfeng Zhang; Zhenhuan Jiao; Zhao Yang; Shaohui Chu; Jinfei Chai; Song Zhang; Lunkai Gong; Hongyu Cui (Buildings, 2025)
Significant progress has been made in the low-temperature toughness and crack resistance of polypropylene fiber-reinforced composites. However, there is still a gap in the research on damage evolution under freeze–thaw cycles and complex stress ratios. To solve the problem of durability degradation of traditional rubble masonry in cold regions, this paper focuses on the study of polypropylene fiber-mortar-masonry blocks with different fiber contents. Using acoustic emission and digital image technology, the paper conducts a series of tests on the scaled-down polypropylene fiber-mortar-masonry structure, including uniaxial compressive tests, three-point bending tests, freeze–thaw cycle tests, and tests with different stress ratios. Based on the Kupfer criterion, a biaxial failure criterion for polypropylene fiber mortar-masonry stone (PPF-MMS) was established under different freeze–thaw cycles. A freeze–thaw damage evolution model was also developed under different stress ratios. The failure mechanism of PPF-MMS structures was analyzed using normalized average deviation (NAD), RA-AF, and other parameters. The results show that when the dosage of PPF is 0.9–1.1 kg/m3, it is the optimal content. The vertical stress shows a trend of increasing first and then decreasing with the increase in the stress ratio, and when α = 0.5, the degree of strength increase reaches the maximum. However, the freeze–thaw cycle has an adverse effect on the internal structure of the specimens. Under the same number of freeze–thaw cycles, the strength of the specimens without fiber addition decreases more rapidly than that with fiber addition. The NAD evolution rate exhibits significant fluctuations during the middle loading period and near the damage failure, which can be considered precursors to specimen cracking and failure. RA-AF results showed that the specimens mainly exhibited tensile failure, but the occurrence of tensile failure gradually decreased as the stress ratio increased.